Effect of moisture on solid state stability - Srčič, Stanko; Lavrič, Zoran (Journal of Medical Science, 2023)
Water is omnipresent during pharmaceutical product manufacturing and may interact with the drug substance, excipients, and the drug product in either solvent or vapor form, resulting in several physico-chemical changes, ultimately affecting product performance. Therefore, understanding the mechanisms behind such moisture-induced changes is necessary at every stage of pharmaceutical development and manufacturing to obtain the target formulation.Characterization tools, such as water sorption, spectroscopy, thermal analysis, diffraction, and more sophisticated approaches like simulations and PAT techniques, can help in the selection of the appropriate solid form, manufacturing method, excipients, and storage conditions, enabling the manufacturing of a stable drug product formulation.
Keywords: water-solid interactions; physico-chemical changes of solids; drug products stability; drug products bioavaiability